ANALISIS POTENSI WISATA RELIGI KI MEROGAN PALEMBANG - Panorama, Maya (Islamic Economics Program, Faculty of Islamic Economics and Business, 2018)
Palembang as a city that famous as commercial city and culinary tour city. But other potentials of Palembang City are religious tourism such as Ki Merogan Mosque tour. This attractions are already famous in the world of tourism but still need development to attract more tourists. This study identifies how the perception of tourists to this attraction and see the potential and provide development strategies in accordance with the needs and desires of tourists. Using 200 sample people consisting of tourists who have visited Ki Merogan tourism by accidental sampling. Techniques use by explorative qualitative analysis to reveal the potential that exists in both attractions. The result of the research using SWOT analysis shows that Ki Merogan tourism object is in quadrant I which means in growing and developing /aggressive position. Development strategy that is suitable for both attractions such us increase tourist attractions and addition on tourist infrastructure such as restaurants, villas, comfort toilets, manage community tourism in develop the attractions. Tourism management must also be managed more professionally to generate profit.